Mortalidade infantil por causas no Estado de São Paulo (Brasil) em 1983: análise sob a perspectiva das causas múltiplas de morte Infant mortality by causes in the State of S.Paulo (Brazil) in 1983: analysis under the perspective of multiple causes of death - Paulo Murad Saad (Universidade de São Paulo, 1986)
Objetivou-se apresentar a mortalidade infantil por causas no Estado de São Paulo, Brasil, com base nos dados de 1983 obtidos a partir da classificação por causas múltiplas de morte, disponíveis desde a implantação do Sistema de Classificação Automática de Causas de Morte. Detectaram-se dois tipos de casos bem definidos: os óbitos ocorridos predominantemente no período neonatal, e cujo processo mórbido envolve quase que exclusivamente as afecções pertencentes ao Capítulo das Perinatais da Classificação Internacional de Doenças; e os óbitos ocorridos principalmente no período pós-neonatal, em cujo processo mórbido aparecem mencionadas significativamente as infecções intestinais, a septicemia, a desnutrição, a desidratação e a broncopneumonia. O estudo da associação entre as principais causas de morte mostrou, por um lado, a imaturidade e a prematuridade fortemente relacionadas com as afecções respiratórias do recém-nascido e com as infecções específicas do período perinatal; e por outro lado, um complexo inter-relacionamento entre as outras cinco causas mencionadas. An analysis of child mortality by causes was made on the basis of classification by multiple causes of death. For this archives containing records of child deaths in the State of S.Paulo (Brazil) for 1983 were used. The underlying cause and the associated causes, according to various clustering types, were, among other variables, retrieved from each record. Two types of cases with clearly determined characteristics were detected: those occurring predominantly during the neonatal period with the morbid process involving almost exclusively diseases in the Perinatal chapter (Chapter XV of the International Classification of Diseases, 9th Revision), and those occurring after the neonatal period with their morbid process showing a significant presence of intestinal infections, septicemia, malnutrition, dehydration and bronchopneumonia. An analysis of M/B ratios, between the number of mentions of each cause and the number recorded as the underlying cause, shows the importance of the study by multiple causes of death in order to avoid the underestimation of the incidence of some diseases that represent more frequently a terminal phase of the morbid process, and are thus mentioned mainly as associated causes. The study of the association of the main causes of death, using a measure of association called "Yule's Q", revealed that the respiratory diseases of the newborn as well as the specific infections of the perinatal period are intimately linked to immaturity and prematurity. It revealed, at the same time, the existence of a complex interrelationship between the 5 most frequent causes in the post-neonatal period, since one of them always occurs significantly associated with at least one of the others in the same group.